Pictorial encyclopedia of modern Japan. - Gakush¯u Kenky¯usha. (Tokyo, Japan Gakken, 1986)
Economic development - Industry - Statistics on population, primary and secondary industries, trade, etc. ; Housing - Family - Work - Leisure - Festivals.
Keywords: Japan -- History -- 1945-1989.; Japan -- History -- 1945-1989 -- Pictorial works